1969
DOI: 10.1037/h0026947
|View full text |Cite
|
Sign up to set email alerts
|

Retention of visual and name codes of single letters.

Abstract: If a stored letter can be matched more rapidly with a physically identical letter (e.g., AA) than it can with a letter having only the same name (e.g., Aa), then the stored representation must preserve something of the visual aspect of the letter. Immediately after the presentation of a letter, a physical match is about 90 msec. faster than a name match and this difference is lost after 2 sec. An interpolated information processing task abolished the difference between physical and name match RTs, but visual n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
248
3
1

Year Published

1977
1977
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(266 citation statements)
references
References 13 publications
13
248
3
1
Order By: Relevance
“…Demonstrations that psychophysical judgments made on patterns that are imagined are often similar to judgments made on patterns that are observed (Posner, Boies, Eichelman, & Taylor, 1969;Shepard & Podgorny, 1978) suggest that images and physical objects may be functionally equivalent at specific levels of the visual system. It has been suggested that, at such levels, mental images might activate processing mechanisms in the visual system directly, substituting for or competing with external visual information (Kerst & Howard, 1978;Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978;Segal & Fusella, 1970).…”
mentioning
confidence: 93%
“…Demonstrations that psychophysical judgments made on patterns that are imagined are often similar to judgments made on patterns that are observed (Posner, Boies, Eichelman, & Taylor, 1969;Shepard & Podgorny, 1978) suggest that images and physical objects may be functionally equivalent at specific levels of the visual system. It has been suggested that, at such levels, mental images might activate processing mechanisms in the visual system directly, substituting for or competing with external visual information (Kerst & Howard, 1978;Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978;Segal & Fusella, 1970).…”
mentioning
confidence: 93%
“…For verbal stimuli, use of a visual short-term store has been demonstrated by testing recognition latencies (e.g., Posner, Boies, Eichelman, & Taylor, 1969). Use of a visual store for immediate recall of verbal stimuli has been demonstrated by testing supraspan lists of consonants (Laughery, Welte, & Spector, 1973) and by testing Chinese speakers for recall of Chinese ideographs (Yik, 1978).…”
mentioning
confidence: 99%
“…For example, in one of the earliest demonstrations of image-percept interaction, Perky (1910) showed that while intentionally imagining an object, subjects were less able to detect a brief visual presentation of that object as compared with cases where imagery was absent (see also Neisser, 1976;Posner, Boies, Eichelman, & Taylor, 1969). More modern replications of the Perky effect have repeatedly shown that visual detection (e.g., Segal, 1971;Segal & Fusella, 1970) and discrimination (e.g., Craver-Lemley & Reeves, 1992; Craver-Lemley, Arterberry, & Reeves, 1997;Reeves, 1981) are impaired by visual imagery (see also Craver-Lemley, Arterberry, & Reeves, 1999).…”
mentioning
confidence: 99%